Nearly monodisperse unimolecular micelles via chloro-based atom transfer radical polymerization. (August 2021) - Li, Zepeng; Senthil, Kannan; Sun, Yawei; Wang, Yi; Huo, Haohui; Hao, Yanyun; Liu, Yutong; Chen, Hongfei; Li, Hui; Zhang, Zhiyue; Ungar, Goran; Zhang, Qilu; et al.
Abstract: Fabrication of unimolecular micelles with uniform sizes and well-controlled structure is currently a big challenge. Herein, we report an easy-to-handle protocol for the preparation of nearly monodisperse unimolecular micelles via atom transfer radical polymerization (ATRP) mediated by chloroacetylated initiator and chloride catalyst (Cl-ATRP). In contrast to Br-ATRP employing bromoacetylated initiator and CuBr as catalyst, Cl-ATRP can significantly suppress chain coupling during the synthesis of unimolecular micelles and result in well-defined polymers with low molar mass dispersity ( Ð < 1.10) even at high monomer conversions ( e.g. ~80%) and extended reaction times. In addition, effort was made to inhibit the formation of linear polymer side products (typical for ATRP of unimolecular micelles). With the optimized protocol, no linear polymer could be detected by size exclusion chromatography (SEC). The obtained nearly monodisperse unimolecular micelles may find application in, e.g. cargo delivery and bio-imaging as also demonstrated in this report. Considering its superior control in ATRP, the easily utilized Cl-ATRP protocol could be extended to the ATRP of, e.g. brush polymers and comb-like polymers where high local radical concentration needs to be avoided. Graphical abstract: Image, graphical abstract